ILF2 Directly Binds and Stabilizes CREB to Stimulate Malignant Phenotypes of Liver Cancer Cells - Hui Du; Yun Le; Fenyong Sun; Kai Li; Yanfeng Xu (Analytical Cellular Pathology)
Cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB) is overexpressed and has an oncogenic role in hepatocellular carcinoma (HCC). Interleukin enhancer binding factor 2 (ILF2) has become research hotspot in liver cancer recently. However, it is still unclear whether and how CREB and ILF2 interact with each other. And how this interaction exerts its role in occurrence and development of liver cancer is still unclear. Here, we found that ILF2 directly bound with CREB, and this binding was essential for the malignant phenotypes of liver cancer cells. Moreover, we found that ILF2 acted as one of the upstream proteins of CREB and promoted CREB only in the protein level, whereas ILF2 expression was not regulated by CREB. Mechanistically, ILF2 bound to the pKID domain of CREB and stimulated its phosphorylation at Ser133. Taken together, our study finds a novel interaction between CREB and ILF2 in liver cancer, and this interaction might play a role in the diagnosis and remedy of liver cancer.